Geochemical records and environmental analysis of the Ediacaran-Cambrian boundary in Eastern Yunnan, South China - Yang, Xuan; Chang, Chao; Chen, Yanlong; Topper, Timothy; Liu, Fan; Liang, Yue; Fang, Ruisen; Zhang, Zhifei (Frontiers in Earth Science, 2023)
East Yunnan is a region of utmost importance in the study of the Ediacaran-Cambrian transition. Although strata from this region have been well studied, recognition of the base of the Cambrian continues to be controversial. This paper presents, a carbon chemostratigraphic isotope and trace element profile through the Dengying and Zhujiaqing formations in the Sujiawa section in East Yunnan. Through carbon isotope and trace element analyses of the Dengying and Zhujiaqing formations we attempt to regionally correlate the section and discuss the paleo-marine redox environment changes during this period. The Fe content of samples is low and the Mn/Sr ratios of the majority of the Sujiawa section samples is lower than 10 and shows no correlations with δ13Ccarb and δ18Ocarb values, indicating that the samples retain near-primary δ13Ccarb characteristics. The carbon isotope profile from the Sujiawa section, shows a prominent negative δ13Ccarb in the basal Zhongyicun Member (N1, -7.3‰) that most likely represents the prominent negative excursion recorded in Ediacaran-Cambrian strata across the world. REE patterns and Y/Ho ratios were used to screen samples, to ensure that the primary seawater REE features and Ce anomalies were preserved. The samples satisfying this screening process show seawater-like REE distribution patterns in leached carbonates and may have recorded Ce anomalies of the seawater from which the carbonates precipitated. These data show that the Baiyanshao Member has Ce/Ce* values between 0.57 and 0.88, the Daibu Member between 0.56 and 0.83, and the Zhongyicun Member between 0.60 and 0.96. The Ce anomalies through the section indicates that the region experienced suboxic-oxic-anoxic conditions throughout the Ediacaran-Cambrian period. Carbon isotope and trace element analyses indicate that the strata record a negative carbon isotope excursion event and anoxic conditions during the period of deposition. This study complements the carbon chemostratigraphic information and trace element data in the region and provides valuable clues for understanding the lithofacies changes through the Ediacaran and Cambrian in different regions of South China.